PROTECTIVE EFFECTS OF TWO CONSTITUENTS OF CHINESE HERBS ON SPINAL MOTOR NEURONS FROM EMBRYONIC RATS WITH HYPOXIA INJURY - Chen, Jian-feng; Fan, Jian; Tian, Xiao-wu; Tang, Tian-si (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Neuroprotective agents are becoming significant tools in the repair of central nervous system injuries. In this study, we determined whether ginkgolides (Gin,extract of GinkgoBiloba) and Acanthopanax senticosus saponins (ASS,flavonoids extracted from Acanthopanax herbal preparations) have protective effects on rat spinal cords exposed to anoxia and we explored the mechanisms that underlie the protective effects. Spinal motor neurons (SMNs) from rat spinal cords were obtained and divided into five groups with 10 wells in each group. In control group, SMNs suffered no injury under normal oxygen; in hypoxia- inducible (HI) group, SMNs suffered injury from hypoxia; in Gin group, 37.5μg/ml Gin were used before 24 hrs of hypoxia; in ASS group, 50μg/ml ASS were used before 24 hrs of hypoxia;in glial cell- lined derived neurotrophic factor (GDNF) group, 0.1μg/ml GDNF were used before 24 hrs of hypoxia. Changes in morphology, neuron viability, and lactate dehydrogenase (LDH) release were observed. In addition, the expression of HIF-1α induced by hypoxia was measured. The neuronal viability in the Gin, ASS, and GDNF pretreated groups was higher than that in the HI group ( P<0.05). The viability in the Gin group was better than that in the ASS group ( P<0.05), but there was no significant difference between the ASS and GDNF groups ( P>0.05). The quantity of LDH released in the three pretreated groups was lower than that in the HI group ( P<0.05). The expression of HIF-1α in the HI group was greater than that in the control group ( P<0.05), and the expression in the three pretreated groups was greater than that in the HI and the control groups ( P<0.05). Our results indicate that Gin and ASS which was not as effective as Gin, but its effects were similar to those of GNDF could all enhance the viability of SMNs and have protective effects on hypoxic neurons.